COVID-19 AND INTERNATIONAL POLITICS: UNDERSTANDING (INTER)DEPENDENCY THROUGH VACCINES PRODUCTION AND DISTRIBUTION - Elyzabeth Bonethe Nasution; Chrystle Feodore Manlee; Cornelia Kristian; Jezzania Verlyn Christy (AEGIS : Journal of International Relations, 2022)
Covid-19 pandemic has opened a new chapter in the International Relations sphere. Its spread is accelerated by the advancement of technology that only globalization has made possible. Among several measures to survive, vaccines are perceived as critical and controversial. The objective of this research is to grasp a better understanding from different perspectives of stakeholders in International Relations, regarding interdependence between developing and developed countries in the international system, using the vaccine. In doing so, this research also analyzes the dynamics in the ASEAN context. Neoliberalism serves as the ore theoretical framework alongside the concepts of interdependence and international cooperation. This research is a qualitative one, using mostly primary data that is gathered from an interview with academicians, researchers, government officials, and students – and secondary data. The results show that the ongoing pandemic has directed developing countries to depend on developed countries with capabilities in vaccines production, including ASEAN member states. The fact that vaccines are even used as a political instrument is found ill-fitted. However, there is still confident that this dependency will move to interdependency once developing countries have found effective strategies in coping with the situation – and it has started.